2014
DOI: 10.1002/ijc.29301
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome instability in diffuse large B cell lymphomas is suppressed by activation of the noncanonical NF‐κB pathway

Abstract: Diffuse large B cell lymphoma (DLBCL) is the most common form of lymphoma in the United States. DLBCL comprises biologically distinct subtypes including germinal center-like (GCB) and activated-B-cell-like DLBCL (ABC). The most aggressive type, ABC-DLBCL, displays dysregulation of both canonical and noncanonical NF-κB pathway as well as genomic instability. Although, much is known about the tumorigenic roles of the canonical NF-kB pathway, the precise role of the noncanonical NF-kB pathway remains unknown. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
(70 reference statements)
0
17
0
Order By: Relevance
“…Extranodal MZL, characterized by t(11;18)(q21;q21)/API2-MALT, depends on NF-κB to inhibit DNA damage-induced and p53-mediated apoptosis [68]. In ABC-DLBCL, NF-κB binds to the promoter regions of GADD45α and REDD1 and regulates these molecules through collaborating with p53 to mediate cyclin G2 expression, suggesting a central role for NF-κB in maintaining genomic integrity and prevention of apoptosis [69]. …”
Section: Nf-κb Signaling and Apoptotic Pathwaysmentioning
confidence: 99%
“…Extranodal MZL, characterized by t(11;18)(q21;q21)/API2-MALT, depends on NF-κB to inhibit DNA damage-induced and p53-mediated apoptosis [68]. In ABC-DLBCL, NF-κB binds to the promoter regions of GADD45α and REDD1 and regulates these molecules through collaborating with p53 to mediate cyclin G2 expression, suggesting a central role for NF-κB in maintaining genomic integrity and prevention of apoptosis [69]. …”
Section: Nf-κb Signaling and Apoptotic Pathwaysmentioning
confidence: 99%
“…Nuclear factor-κB (NF-κB) is an important signal transduction pathway associated with cell proliferation, apoptosis, tumor treatment, and immune regulation (2)(3)(4). Abnormal activation of NF-κB signal transduction is considered a significant feature of DLBCL (5)(6)(7), and was found to be correlated with many clinicopathological features, prognosis and response to therapy in lymphomas.…”
Section: Introductionmentioning
confidence: 99%
“…The Tyr42-phosphorylated IkBa may not be degraded and is bound to the SH2 domain of the regulatory PI3K subunit p85, thus unmasking NF-kB and allowing it to translocate to the nucleus (19). Doxorubicin and H 2 O 2 , atypical NF-kB activators, potentially induce REDD-1 expression (8,35), suggesting that REDD-1 is involved in the proteolysis-independent activation of NF-kB. Concordantly, our data showed that REDD-1 did not induce proteasomal degradation of IkBa and its phosphorylation at Tyr42, but rather stimulated phosphorylation at Ser536 and Ser276 of the NF-kB p65 liberated from IkBa.…”
mentioning
confidence: 99%